2014
DOI: 10.1186/1471-2261-14-154
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting clinical evidence for market authorisation of cardio-vascular devices in Europe and the USA: a systematic analysis of 10 devices based on Austrian pre-reimbursement assessments

Abstract: BackgroundEuropean medical device regulation is under scrutiny and will be re-regulated with stricter rules concerning requirements for clinical evidence for high-risk medical devices. It is the aim of this study to analyse the differences between Europe and USA in dealing with risks and benefits of new cardio-vascular devices.MethodsSince no information is available on clinical data used by the Notified Body for CE-marking, data from Austrian pre-reimbursement assessments close to European market approval wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Although pharmaceuticals enter the European market at one time, medical devices and procedures enter the European health care market in a time span of 1 to 5 (and even more) years after European conformity marking [29,30]. The time taken for the diffusion of medical devices across countries has an important impact on the aim to reduce redundancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although pharmaceuticals enter the European market at one time, medical devices and procedures enter the European health care market in a time span of 1 to 5 (and even more) years after European conformity marking [29,30]. The time taken for the diffusion of medical devices across countries has an important impact on the aim to reduce redundancy.…”
Section: Discussionmentioning
confidence: 99%
“… 22 In a study of 10 devices reimbursed in Austria, Wild and colleagues found that evidence available at the time of CE marking are more often case series or small feasibility trials, compared with the controlled trials and large prospective cohort studies used as the basis for FDA approval. 41 In turn, low rates of publication and lack of high quality evidence may adversely impact patient outcomes. Nieuwenhuijse and colleagues found that innovative and well known hip and knee replacement prostheses were widely implanted despite a lack of high quality evidence supporting their use; several of these devices were also associated with inferior survival and higher rates of revision.…”
Section: Discussionmentioning
confidence: 99%
“…NBs as private companies not only compete from a pricing standpoint for approval contracts, but may be reluctant to disapprove devices for fear of losing an ongoing relationship with a manufacturer who hires them. A lack of centralization makes safety data more difficult to collate, and in any case, data submitted for high-risk devices to the NBs is considered “commercially confidential,” and is not available to the public 2 , 41 , 42 .…”
Section: European Regulation Of Devicesmentioning
confidence: 99%
“…Controversy persists about the differences in U.S. and EU regulatory processes, costs, and the time it can take for a DAD to proceed from concept to approval under the regulations of each. A frequently held assertion is that slower FDA approval processes deprive American citizens of effective DADs that are available to Europeans (2) , and critics have characterized FDA processes as “slow, risk averse, and expensive” (3) . However, the Institute of Medicine determined that current FDA pre-marketing procedures for medical devices are insufficient to assure device safety, particularly those approved largely on their similarity to previously cleared “predicate” devices, rather than on prospective, randomized clinical trials (4) .…”
mentioning
confidence: 99%